Diurnal temperature variations affect development of a herbivorous arthropod pest and its predators. - Dominiek Vangansbeke; Joachim Audenaert; Duc Tung Nguyen; Ruth Verhoeven; Bruno Gobin; Luc Tirry; Patrick De Clercq (PLoS ONE, 2015)
The impact of daily temperature variations on arthropod life history remains woefully understudied compared to the large body of research that has been carried out on the effects of constant temperatures. However, diurnal varying temperature regimes more commonly represent the environment in which most organisms thrive. Such varying temperature regimes have been demonstrated to substantially affect development and reproduction of ectothermic organisms, generally in accordance with Jensen's inequality. In the present study we evaluated the impact of temperature alternations at 4 amplitudes (DTR0, +5, +10 and +15°C) on the developmental rate of the predatory mites Phytoseiulus persimilis Athias-Henriot and Neoseiulus californicus McGregor (Acari: Phytoseiidae) and their natural prey, the two-spotted spider mite Tetranychus urticae Koch (Acari: Tetranychidae). We have modelled their developmental rates as a function of temperature using both linear and nonlinear models. Diurnally alternating temperatures resulted in a faster development in the lower temperature range as compared to their corresponding mean constant temperatures, whereas the opposite was observed in the higher temperature range. Our results indicate that Jensen's inequality does not suffice to fully explain the differences in developmental rates at constant and alternating temperatures, suggesting additional physiological responses play a role. It is concluded that diurnal temperature range should not be ignored and should be incorporated in predictive models on the phenology of arthropod pests and their natural enemies and their performance in biological control programmes.